Can Unilateral Strength Training Optimize Change of Direction Mechanics and Mitigate Anterior Cruciate Ligament Injury Risk in Female Soccer Players? A Preliminary Pre–Post Intervention Study - Alice Rogalski; Ayrton Moiroux-Sahraoui; Maria Stergiou; Maxence Pieulhet; Maurice Douryang; Florian Forelli (Sports)
Background: Anterior cruciate ligament (ACL) injuries are a major concern in female soccer players, with change of direction (COD) movements being a key contributor to non-contact injuries. Traditional injury prevention programs have shown limited effectiveness in addressing individual biomechanical deficits. This study aimed to evaluate the effects of a 10-week unilateral strength training program on COD mechanics and ACL injury risk factors. Methods: Eleven female soccer players participated in a pre–post intervention study. Movement mechanics was assessed using the Cutting Movement Assessment Score (CMAS) at 45°, 75°, and 90° angles. The training program included unilateral lower limb strengthening exercises designed to enhance neuromuscular control and reduce biomechanical risk factors. Risk profiles were analyzed before and after the intervention. Statistical analyses included paired t-tests and effect size calculations. Results: Significant improvements in CMAS scores were observed at all COD angles (p < 0.05), with the largest effect at 90° (Cohen’s d = 2.1). The percentage of high-risk players decreased from 82% to 0%, while the proportion of low-risk players increased from 36% to 73%. Improved knee alignment, foot placement, and trunk stability were key contributors to the observed movement enhancements. Conclusions: Unilateral strength training may effectively improve COD mechanics and reduces biomechanical risk factors associated with ACL injuries in female soccer players. Our findings suggest that individualized training interventions can influence current injury prevention strategies.